A new approach to audience segmentation for vaccination messaging: applying the anger activism model. Issue 4 (3rd August 2021) - Jang, Youjin; Turner, Monique Mitchell; Heo, Ruth Jinhee; Barry, Rachel
Abstract : Purpose: This study aims to use the anger activism model as an audience segmentation tool in the context of the anti-vaccination movement. Design/methodology/approach: A cross-sectional survey was conducted with a national purposive sample ( N = 438). Findings: The group with high anger, strong efficacy (i.e. "activists") was found to be more likely to engage in information seeking and was more accurate and defense-motivated when examining information about anti-vaxxers compared to other groups. Importantly, activists were more likely to engage in both low and high commitment behaviors to change vaccine policy. Originality/value: As anti-vaxxers have proven to be difficult to change attitudinally, future campaigns are more likely to succeed if they leverage pro-vaccine audiences to fight for change. However, the understanding of the various segments within the pro-vaccination audience is limited. The data are discussed regarding leveraging high anger, strong efficacy audiences as change agents in future persuasive campaigns.